A Smoothed Particle Hydrodynamics Method for the Simulation of Centralized Sloshing Experiments - Vorobyev, Alexander (KIT Scientific Publishing, 2013)
The Smoothed Particle Hydrodynamics (SPH) method is proposed for studying hydrodynamic processes related to nuclear engineering problems. A problem of possible recriticality due to the sloshing motions of the molten reactor core is studied with SPH method. The accuracy of the numerical solution obtained in this study with the SPH method is significantly higher than that obtained with the SIMMER-III/IV reactor safety analysis code.